Coactivator-Associated Arginine Methyltransferase 1 (CARM1) Is a Positive Regulator of the Cyclin E1 Gene - Messaoudi, Selma El; Fabbrizio, Eric; Rodriguez, Carmen; Chuchana, Paul; Fauquier, Lucas; Cheng, Donghang; Theillet, Charles; Vandel, Laurence; Bedford, Mark T.; Sardet, Claude (Proceedings of the National Academy of Sciences - PNAS, 2006)
The Cyclin El gene (CCNE1) is an ideal model to explore the mechanisms that control the transcription of cell cycle-regulated genes whose expression rises transiently before entry into S phase. E2F-dependent regulation of the CCNE1 promoter was shown to correlate with changes in the level of H3-K9 acetylation/methylation of nucleosomal histones positioned at the transcriptional start site region. Here we show that, upon growth stimulation, the same region is subject to variations of H3-R17 and H3-R26 methylation that correlate with the recruitment of coactivator-associated arginine methyltransferase 1 (CARM1) onto the CCNE1 and DHFR promoters. Accordingly, CARM1-deficient cells lack these modifications and present lowered levels and altered kinetics of CCNE1 and DHFR mRNA expression. Consistently, reporter gene assays demonstrate that CARM1 functions as a transcriptional coactivator for their E2F1/DP1-stimulated expression. CARM1 recruitment at the CCNE1 gene requires activator E2Fs and ACTR, a member of the p160 coactivator family that is frequently overexpressed in human breast cancer. Finally, we show that grade-3 breast tumors present coelevated mRNA levels of ACTR and CARM1, along with their transcriptional target CCNE1. All together, our results indicate that CARM1 is an important regulator of the CCNE1 gene.